1997
DOI: 10.1124/mol.52.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Type 1α Metabotropic Glutamate Receptor-Stimulated Phosphoinositide Signaling after Pertussis Toxin Treatment

Abstract: SUMMARYThe regulation of phosphoinositide hydrolysis by the type 1␣ metabotropic glutamate receptor (mGluR1␣) was investigated in stably transfected baby hamster kidney (BHK) cells. Incubation of the cells with L-glutamate, quisqualate, and 1-aminocyclopentane-1S,3R-dicarboxylic acid resulted in a marked accumulation of 3 H]InsP 1 responses were similar in control and PTXtreated BHK-mGluR1␣ cells. These changes in the concentration-effect curves for mGluR agonists are consistent with a model in which the recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
2
14
1
Order By: Relevance
“…The coupling of group I mGluR to PI-PLC, as demonstrated by inositol phosphate measurements, has been shown in many systems (Abe et al, 1992;Aramori & Nakanishi, 1992;Carruthers et al, 1997;Wakelam, 1998). Here we show that there was no detectable increase in IP 3 in synaptosomes within 15 s of receptor stimulation, a time point at which we can measure an elevated IP 3 response to carbachol in cerebellar granule cells (del Rio et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The coupling of group I mGluR to PI-PLC, as demonstrated by inositol phosphate measurements, has been shown in many systems (Abe et al, 1992;Aramori & Nakanishi, 1992;Carruthers et al, 1997;Wakelam, 1998). Here we show that there was no detectable increase in IP 3 in synaptosomes within 15 s of receptor stimulation, a time point at which we can measure an elevated IP 3 response to carbachol in cerebellar granule cells (del Rio et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…PI-PLC activation is conventionally measured as an increase in IP 3 or DAG concentration, the two products of PIP 2 hydrolysis by PLC. mGluRs activate PI turnover with fast kinetics (Aramori & Nakanishi, 1992;Carruthers et al, 1997), therefore, we measured IP 3 after 15 s. However, we could not detect any change in IP 3 levels by receptor stimulation with either 1 mM quisqualate (a non-selective mGluR agonist) or 100 mM 1S,3R-ACPD (Figure 4). This method however has been successfully employed to demonstrate an elevation of IP 3 in carbachol stimulated cerebellar granule cells (del Rio et al, 1998).…”
Section: Mglur Coupling To Pi-plc In Synaptosomesmentioning
confidence: 89%
“…lA). However, preaddition of GPT (3 U ml~' ) and pyruvate (3 mM) to decrease the concentration of glutamate in the incubation medium (Desai et al, 1995;Carruthers et al, 1997) was found to inhibit completely this basal increase, suggesting that endogenous glutamate released from the cells can have a stimulatory effect when the hmGlula receptor is expressed at high levels (data not shown). Furthermore, the increased basal 3H-InsP level measured in IPTG-induced cells was also found to be inhibited by the mGlu receptor antagonist 4-C3HPG (used at 300 ‚uM).…”
Section: Late Treatment Of the Cells With 100mentioning
confidence: 99%
“…Determination of basal and agonist-induced accumulation of 3H-InsP in CHO-lac-hmGlula cells was performed as previously described (Carruthers et al, 1997). When required, IPTG was added directly to the culture medium for the times indicated.…”
Section: H-labelled Inositol Phosphate (3h-insp) Quantificationmentioning
confidence: 99%
“…However, this coupling applies to rat mGlu1 receptors, whereas human mGlu1␣ and -␤ receptors seem to be coupled to PI hydrolysis with equal efficacy (Stephan et al, 1996). The mGlu1␣ receptor but not the mGlu1␤ or mGlu1␥ receptor is constitutively active in stimulating PI hydrolysis; i.e., it is active in the absence of an orthosteric agonist, in transfected LLC-PK1, HEK-293, or BHK cells (Joly et al, 1995;Prézeau et al, 1996;Carruthers et al, 1997;Mary et al, 1997;Hiltscher et al, 1998). This constitutive activity is not prevented by orthosteric mGlu1 receptor antagonists, which reduce the response to applied glutamate, but not the basal activity; hence, this activity is not triggered by endogenous glutamate present in the culture medium (Prézeau et al, 1996).…”
Section: A G-protein Couplingmentioning
confidence: 99%